Pre and postoperative imaging in patients undergoing pyeloplasty: A survey of current adult and paediatric practice. Issue 2 (May 2022) - Bianco, Marta; Castagnetti, Marco; Masieri, Lorenzo; Mele, Ermelinda; Gennaro, Mario DE
Background: Imaging to be used during the workup and follow-up of patients undergoing pyeloplasty is still controversial. Present survey aimed at assessing variations in pre- and post-operative imaging between adults and paediatric specialists in patients undergoing pyeloplasty. Methods: A survey of members of the 'Italian Society of Urology' (SIU) and the 'Italian Society of Paediatric Urology' (SIUP) was conducted using an online platform. Results: Respondents included 87 (74.4%) adult and 30 (25.6%) paediatric specialists. Adult specialists were significantly more likely to use a CT scan during preoperative workup ( p  = 0.001) and postoperative follow-up ( p  < 0.001). In contrast, paediatric specialists were significantly more likely to recommend voiding cystourethrography during the workup ( p  < 0.001) and an MRI in cases requiring additional diagnostic study (<0.001). Adult specialists reported to deal significantly more commonly with symptomatic or complicated hydronephroses ( p  < 0.001). The majority of respondents recommend an ultrasound scan at 1–3 months as first postoperative investigation. Two-third also recommended a nuclear scintigraphy, but 67.8% of adult specialists recommended to perform it within 6 months of surgery whereas 76.7% of paediatric specialists between 6 and 12 months ( p  < 0.001). Conclusions: Present survey suggests quite a significant variation between adult and paediatric specialists in pre- and post-operative assessment of patients requiring pyeloplasty. This may just reflect different attitudes that could be improved with appropriate studies, or essential differences in the condition or the characteristics of treated patients. In any case, such differences are important and should be taken into account.